Effect of Single Oxide Fluxes on Morphology and Mechanical Properties of ATIG on 316 L Austenitic Stainless Steel Welds - Hdhibi, A.; Touileb, K.; Djoudjou, R.; Ouis, A.; Bouazizi, M. L.; Chakhari, J. (Engineering, Technology & Applied Science Research, 2018)
Tungsten inert gas (TIG) is a wide common process used in fabrication due to its low cost equipment, high quality and accuracy welds but has low productivity related to the low penetration depth in single pass. A new perspective, the Activated Tungsten Inert Gas (ATIG), in which the same equipment as TIG is used, except that a thin layer of activated flux is deposited on a workpiece surface. In this work, eight kinds of oxides were tested on 316L austenitic stainless steel. Three levels of welding current were used to study the effect of different activating fluxes on weld bead geometry and mechanical properties. X-ray Photoelectron Spectroscopy (XPS) was used for the first and the second level energy for different ATIG welds to analyze the relationship between the weld shape and oxygen content in welds. The experimental results showed that the weld profile is related to the thermodynamic stability of selected oxides and in relation to the energy provided. ATIG with TiO2, SiO2, MnO2 oxides presented the deepest welds followed by Cr2O3, Fe2O3, and ZnO. Finally ZrO2, CaO oxides had no effect on the weld depth. The ATIG welded joint showed better tensile strength than TIG. The ATIG hardness measurements carried out showed also better if not the same as TIG weld except for the Silicon oxide weld. Results of the impact test showed that, except for the titanium dioxide TiO2 which has a good benefit, the weldment using the other oxide fluxes exhibits worse withstanding to sudden shock than TIG welding.